(untitled) (Cadernos de Sociomuseologia, 2020)
Under objectivist communication premise, the political power reproduces its ideology through diverse social layers and pilars that consciously or unconsciously embrace it. Behind this impartiality cloak lives the normalisation of violence and its subsequent permanence over daily life. The epistemological opening of representations put the current social order under dispute. Considering the subjectivity of feelings and emotions as part of the process of raising political awareness, allows us to put Sociomuseology side by side with communitarian practical expertise, including photography. It is discussed here, under these concepts, how important it is for the memory repairing act to be welcomed by the public sphere and making its way to invert historical narratives. Keywords: Representation, Ideology, Museology, Sociomuseology, communication.